2020
DOI: 10.3390/jcm9082341
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Urine Metabolomics for Monitoring Renal Allograft Injury and Immunosuppression in Pediatric Patients

Abstract: Despite new advancements in surgical tools and therapies, exposure to immunosuppressive drugs related to non-immune and immune injuries can cause slow deterioration and premature failure of organ transplants. Diagnosis of these injuries by non-invasive urine monitoring would be a significant clinical advancement for patient management, especially in pediatric cohorts. We investigated the metabolomic profiles of biopsy matched urine samples from 310 unique kidney transplant recipients using gas chromatography–m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“… 2 In urine, a recent study by Sigdel TK et al associated three main metabolites (increase in glycine, decrease in N-methylalanine and inulobiose) in the urine with histology proven heterogenous allo-immune dysfunctions of kidney transplants (acute rejections and IFTA). 35 Interestingly, glycine has been associated with broad anti-inflammatory properties, ischemia/reperfusion and thermic shock protection. 36 On the opposite, N-methylalanine was negatively correlated with active inflammation in patients with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In urine, a recent study by Sigdel TK et al associated three main metabolites (increase in glycine, decrease in N-methylalanine and inulobiose) in the urine with histology proven heterogenous allo-immune dysfunctions of kidney transplants (acute rejections and IFTA). 35 Interestingly, glycine has been associated with broad anti-inflammatory properties, ischemia/reperfusion and thermic shock protection. 36 On the opposite, N-methylalanine was negatively correlated with active inflammation in patients with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Sigdel et al [ 64 ] analyzed the metabolomic profiles of biopsy-matched urine samples from 310 KTRs (106 AR). They identified 266 metabolites; a panel of 11 metabolites (glycine, glutaric acid, adipic acid, inulobiose, threose, sulfuric acid, taurine, N-methylalanine, asparagine, 5-aminovaleric acid lactam, and myo-inositol) enabled detection of AR.…”
Section: Omics-based Biomarkers For Allograft Rejection In Kidney Tra...mentioning
confidence: 99%
“…In a recent study, a panel of nine differential metabolites in urine were identified as novel potential metabolite biomarkers of TCMR ( 73 ). The metabolomic biomarkers that considered as potential markers for rejection episodes are listed in Table 1 ( 72 78 ).…”
Section: Potential Biomarkers For Early Diagnosis and Prognosismentioning
confidence: 99%